The Political Foundations of Climate Action: Some Uncomfortable Truths - Chandra Mishra, Satish (Sustainability Science and Resources, 2023)
This paper questions two fundamental political foundations for climate action: that there is but one common humanity and that global warming is the most critical and immediate threat to the survival of humankind. It further argues that the philosophical foundations of climate action lack depth and precision. While ‘climate justice’ appears center-stage to climate action, its conceptual basis remains weak because it has failed to integrate the enormous work done on justice, human rights, equality, governance, democracy and civil society since the mid 19th century. In fact, ‘climate justice’ only makes sense as a part of an overall framework of equality rather than something sui generis. On a political campaign level, this paper argues that too much attention has been paid to global conferences such as the series of COPs culminating in the most recent COP 28 in Dubai. Much less has been done on charting how the dialogue surrounding climate action today is affected by the emergence of global corporations, rapid urbanization, growth of middle-class consumption and the growth of megacities especially in Asia. The paper suggests that it would be more fruitful to focus on the local/community and regional levels to promote familiar technologies and conservation practices rather than on global conferences and their associated statements.